A QUALITATIVE STUDY : UNIVERSITY STUDENTS’ BOOK CHOICES FOR GRAMMAR IN THE ACADEMIC YEAR 2023/2024 (Eduscotech, 2024)
This study aims to analyze and identify students' needs related to their choice of grammar books, focusing on the analysis of the target situation (necessities, lacks, and wants) to develop an ideal English grammar book that meets students' needs. The participants of the study were undergraduate students from five universities: Universitas Doktor Nugroho Magetan, Universitas STAIM Ma'arif Magetan, IAIN Ponorogo, UIN Malang, and UNU Surakarta. The research method used was descriptive qualitative. Data were collected through observation, questionnaires, and semi-structured interviews, and analyzed using data reduction, data display, and conclusion verification techniques. The results indicate that several main factors influencing students' choice of grammar textbooks include clear language, alignment with learning objectives, cultural relevance, appropriate examples, organized structure, availability in both print and digital formats, diversity of materials, and coverage of essential topics such as punctuation, capitalization, tense consistency, and technology integration.